Does the Diabetic Foot Have a Significant Impact on Selected Psychological or Social Characteristics of Patients with Diabetes Mellitus?. (25th March 2014) - Fejfarová, Vladimíra; Jirkovská, Alexandra; Dragomirecká, Eva; Game, Frances; Bém, Robert; Dubský, Michal; Wosková, Veronika; Křížová, Marta; Skibová, Jelena; Wu, Stephanie
Abstract : The aim of our case-control study was to compare selected psychological and social characteristics between diabetic patients with and without the DF (controls). Methods . 104 patients with and 48 without DF were included into our study. Both study groups were compared in terms of selected psychosocial characteristics. Results . Compared to controls, patients with DF had a significantly worse quality of life in the area of health and standard of living as shown by lower physical health domain (12.7 ± 2.8 versus 14.7 ± 2.5 ; P < 0.001 ) and environment domain (14.1 ± 2.2 versus 15 ± 1.8 ; P < 0.01 ) that negatively correlated with diabetes duration (r = - 0.061 ; P = 0.003 ). Patients with DF subjectively felt more depressed in contrast to controls (24.5 versus 7.3%; P < 0.05 ); however, the depressive tuning was objectively proven in higher percentage in both study groups (83.2 versus 89.6; NS). We observed a significantly lower level of achieved education (P < 0 . 01 ), more patients with disability pensions (P < 0 . 01 ), and low self-support (P < 0 . 001 ) in patients with the DF compared to controls. In the subgroup of patients with a previous major amputation and DF (n = 6 ), there were significantly worse outcomes as in the environment domain (P < 0.01 ), employment status, and stress readaptation (P < 0.01 ) in contrast to the main study groups. Conclusions . Patients with DF had a predominantly worse standard of living. In contrast to our expectations, patients with DF appeared to have good stress tolerability and mental health (with the exception of patients with previous major amputation) and did not reveal severe forms of depression or any associated consequences.